The quest for successful Atlantic salmon restoration: perspectives, priorities, and maxims. (10th November 2021) - Lennox, Robert J; Alexandre, Carlos M; Almeida, Pedro R; Bailey, Kevin M; Barlaup, Bjørn T; Bøe, Kristin; Breukelaar, André; Erkinaro, Jaakko; Forseth, Torbjørn; Gabrielsen, Sven-Erik; Halfyard, Edmund; Hanssen, Erlend M; et al.
Abstract: Atlantic salmon is often a focal species of restoration efforts throughout the north Atlantic and it is therefore an excellent case study for how best to design programmes to address and mitigate threats and correct population declines. This perspective is written to promote the work that has been accomplished towards restoration of Atlantic salmon populations and synthesize how we believe the lessons can be used effectively to support efforts by management agencies to restore populations. We reviewed where restoration is needed for Atlantic salmon, agreed on definitions for three levels of successful restoration, and then applied these criteria to 49 published papers focused on Atlantic salmon restoration. We identified 16 successful examples of restoration among 49 papers reviewed and discussed what interventions led to success versus failure. We then addressed key questions about when hatchery stocking should be used as part of a restoration measure and whether local restoration efforts are enough when these wide-ranging species encounter broad-scale changes in the north Atlantic, specifically related to issues of climate change and to marine survival. We advise to avoid restoration as much as possible by protecting and managing existing populations and when restoration is necessary, problems should be identified and addressed in partnership with river users. With appropriate resources and research to resolve ongoing mysteries, restoration of lost Atlantic salmon populations is absolutely feasible.